Orthoepic competence and its link to phonological and orthographic competences in foreign language teaching - Gabarrón Pérez, Ángel (Pulso. Revista de educación, 2021)
The Common European Framework of Reference for Languages (hereinafter CEFR) and its update, the Complementary Volume with New Descriptors, set out the competencies necessary for the development of the oral and written skills of a foreign language, such as the orthoepic competence, which directly relates both skills and is defined in the CEFR as the correct pronunciation of a language from its written form (Council of Europe, 2002; p. 115). Serious analysis of this competence should not be carried out without taking into account both phonological and orthographic competences and thus establishing a coherent relation between the three of them. Thus, orthoepic competence could be considered as the result of merging both competences into one, which mastery allows the learner to be able to decode the relations between sounds and graphemes and to read words, sentences and texts in the target language correctly. This article aims to analyse this relation and the role of orthoepic competence in the teaching of foreign languages. Finally, we will analyse the activities proposed in the CEFR and the necessary strategies described in the document for its development.